IMPACT SOCIAL MEDIA MARKETING AND BRAND LOYALTY ON PURCHASE DECISION FOR BRAND LOVE KPOP TREASURE MUSIC ALBUMS - Christivany, Christivany; Iskamto, Dedi (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2023)
ABSTRACTThis study aimed to examine the role of brand love as a moderator between the influence of social media marketing and brand loyalty on the choice to buy K-pop Treasure music albums. This research uses a quantitative approach combined with descriptive statistics. The number of research samples was 400 samples using the non-probability sample method. This research uses Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that brand love has a positive and significant effect on purchasing decisions, brand loyalty has a positive and significant effect on brand love, brand loyalty has a positive and significant effect on purchasing decisions, social media marketing has a positive and significant effect on brand love, social media marketing has a positive and significant effect on purchasing decisions. Brand love significantly mediates the relationship between brand loyalty and purchasing decisions, and brand love significantly mediates the relationship between social media marketing and purchasing decisions.ABSTRAKTujuan penelitian ini untuk menguji peran brand love sebagai moderator antara pengaruh social media marketing dan brand loyalty terhadap pilihan membeli album music K-pop Treasure. Penelitian ini menggunakan pendekatan kuantitatif yang dipadukan dengan statistik deskriptif. Jumlah sampel penelitian sebanyak 400 sampel dengan menggunakan metode sampel non-probabilitas. Penelitian ini menggunakan Structural Equation Modeling-Partial Least Square (SEM-PLS). Hasil penelitian menunjukkan bahwa brand love berpengaruh positif dan signifikan terhadap keputusan pembelian, Brand Loyalty berpengaruh positif dan signifikan terhadap brand love, Brand loyalty berpengaruh positif dan signifikan terhadap keputusan pembelian, social media marketing berpengaruh positif dan signifikan terhadap brand love, Social media marketing berpengaruh positif dan signifikan terhadap keputusan pembelian. Brand love signifikan memediasi hubungan antara brand loyalty dan keputusan pembelian, dan Brand love berpengaruh signifikan memediasi hubungan antara social media marketing dan keputusan pembelian.